Drivers and consequences of customer participation into value co-creation: a field experiment - Guzel, Mevludiye; Sezen, Bülent; Alniacik, Umit (Emerald Group Publishing Ltd, 2021)
Purpose This paper aims to analyze value co-creation (VCC) in new product development from consumer's perspective. It offers a holistic approach to consumers' VCC behavior with its before (drivers) and after (consequences) stages. Design/methodology/approach Three consecutive studies are carried out to test the hypotheses examining the antecedents and results of co-creation behavior, as well as the behavior itself in a new headphones design context. The experimental data have been collected from 934 university students within a period of six months. Findings Findings suggest that extraversion and openness to experience increase consumers' willingness to participate in VCC. Celebrity endorsers and product category involvement also affect this tendency. When consumers display co-creation behavior, they intend to purchase the product to be co-created. However, they are especially keen to buy this co-created product when their contributions are embodied in it. Originality/value Previous studies focus on intentions, lacking a detailed analysis of actual VCC behavior. By shedding light on co-creation behavior with its before and after stages, this paper contributes to co-creation literature with a field experiment. Consumers' co-creation behavior has been observed in the context of new product development, which is mostly occupied by business to business research. Therefore, the results also add to research on new product development in business to consumer contexts.
Keywords: Value co-creation; Purchase intention; Satisfaction; Product management; Celebrity endorsement; New product development; Personality traits; Product involvement; Perceived contribution